The interplay of the Dirty Hands of British area bombing and the wicked problem of defeating Nazi Germany in the Second World War – A lesson in leadership ethics. (June 2019) - Sanders, Paul; Grint, Keith
The British area bombing of Germany in the Second World War has provided for enduring ethical controversy. Eschewing conventional approaches, we present area bombing as a Dirty Hands leadership response to the Wicked Problem of Britain's wartime strategic predicament. Using historical methodology, we establish two distinct phases in area bombing: 1942–1944, when this was ethically contentious but politically necessary; and 1944–1945, which lacks a Dirty Hands legitimation. The second phase follows upon a six-month lull in area bombing during Bomber Command's assignment to Overlord (D-Day) duties. It is characterised by credible alternatives to area bombing, a waning sense of proportionality in Bomber Command activity, and intensifying death and destruction without justifiable purpose. We relate the breaching of the boundaries of Dirty Hands in Phase II to a precise date – September 1944. This coincides with the mutation of the strategic Wicked Problem into a Critical Problem, visible in the stalling of the Allied land campaign in France. Mistaking this for a Tame Problem, the C-in-C of Bomber Command, Arthur Harris, exploits the political context to escalate his commitment. Following Watters' alignment of Critical Problems with Virtue Ethics, we argue that Harris' leadership in Phase II is not consistent with Virtue Ethics (of which recognition of the boundaries of Dirty Hands is a function). Harris is the archetype of the leader who gets away with exploiting a Wicked Problem because his superiors have let down their guard. In the final instance, his failure of ethical leadership becomes their own.